UPAYA GURU DALAM MENINGKATKAN MINAT BACA PADA PESERTA DIDIK DI SD NEGERI KUTA JAYA II - Nadila Utami; Encep Andriana; Siti Rokmanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe the efforts of teachers in increasing students' interest in reading at SD Negeri Kuta Jaya II, Tangerang Regency-Banten. This research uses qualitative/descriptive methods. This study involved 5th grade homeroom teachers and students, as research participants. Data were obtained through interviews and observations. The results showed that the interest in reading at SDN Kuta Jaya II is still low, which is caused by internal and external factors. The efforts made by teachers to increase students' interest in reading are by conducting literacy activities 15 minutes before learning, providing a reading corner to support students' reading activities, and acting as a motivator and facilitator for students to increase their desire to read. If the low interest in reading of students is left unchecked, it will affect the sustainable learning outcomes of students. Therefore, increasing students' interest in reading in elementary schools is very important. Keywords: Reading interest, students, elementary school